2015
DOI: 10.5751/es-07601-200315
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the use of local ecological knowledge to monitor hunted tropical-forest wildlife over large spatial scales

Abstract: C. A. Peres. 2015. Evaluating the use of local ecological knowledge to monitor hunted tropical-forest wildlife over large spatial scales. ABSTRACT. Monitoring the distribution and abundance of hunted wildlife is critical to achieving sustainable resource use, yet adequate data are sparse for most tropical regions. Conventional methods for monitoring hunted forest-vertebrate species require intensive in situ survey effort, which severely constrains spatial and temporal replication. Integrating local ecological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 63 publications
1
81
1
5
Order By: Relevance
“…Tropical inland fisheries have also been overexploited (8), yet evidence is based on local effects of rural-subsistence fishing (8,15), so the impacts of overfishing inland waters to supply urban markets are unclear. Modeled bushmeat market data suggesting that rainforest defaunation shadows exist around urban areas (16)(17)(18) are supported by recent empirical evidence that in situ terrestrial wildlife population impacts are greatest nearer small towns (19). Although forest degradation has been observed spreading from a tropical forest metropolis to meet demand for wood (20), the role of emerging metropolises (>1 million people) in driving large-scale wildlife overharvesting in rainforests and/or inland waters is unknown.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Tropical inland fisheries have also been overexploited (8), yet evidence is based on local effects of rural-subsistence fishing (8,15), so the impacts of overfishing inland waters to supply urban markets are unclear. Modeled bushmeat market data suggesting that rainforest defaunation shadows exist around urban areas (16)(17)(18) are supported by recent empirical evidence that in situ terrestrial wildlife population impacts are greatest nearer small towns (19). Although forest degradation has been observed spreading from a tropical forest metropolis to meet demand for wood (20), the role of emerging metropolises (>1 million people) in driving large-scale wildlife overharvesting in rainforests and/or inland waters is unknown.…”
mentioning
confidence: 68%
“…To keep response variables spatially associated with each community's location, each response variable concerned only fishing trips that had occurred within a 2-h rabeta motorized canoe journey from the fisher's home in the community. This is a measure that local people can relate to and that is fairly standard, as most harvesting is undertaken using motorized canoes of similar power (generally 5.5 horsepower) that travel at around 9 km·h −1 (19). Community was used as a random variable in all models.…”
Section: Methodsmentioning
confidence: 99%
“…Hunters' abilities to spot secondary evidence of sitatunga has been key in mapping the species' local distribution, with hunter-aided surveys yielding considerably more data per effort than camera traps (data points/hour of effort: 174/225 = 0.773 versus 34/34,848 = 0.001, respectively). Other authors have similarly found that the efficiency of hunter-led surveys often exceeds that of more conventional survey techniques (Parry and Peres 2015).…”
Section: Discussionmentioning
confidence: 98%
“…It is thus best combined with scientific data collection that corroborates local knowledge and puts it into broader contexts (Gilchrist et al 2005). If done in collaboration with locals, akin to hunter-aided surveys and camera trapping in Avu, such data collection provides opportunities to build mutual trust and respect (Gratani et al 2011) and can instill local communities with a sense of pride, ownership, and financial benefit in the conservation effort (Drew 2005, Parry andPeres 2015). The resulting local motivation for conservation may be the most valuable outcome of engaging in the process of incorporating TEK in conservation management (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation